Identifying Variations in Motor Fitness Components among Upper Primary and Secondary School Male Students - Bhagi, Jupender Singh; Tyagi, Sarita; Kaur, Kuljeet (Physical Education Theory and Methodology, 2024)
Background. Motor fitness helps students develop academically and socially. The students are more engaged in fitness activities with classmates of similar skills. Therefore, motor fitness programs should address kids’ capacity to increase physical activity. Objectives. The study aimed to ascertain variations in upper primary and secondary school male students with respect to selected motor fitness components, i.e. strength (standing broad jump), speed (50-meter sprint) and endurance (800-meter run). Materials and methods. A total of 150 male students, aged 12 to 16, from five schools in Delhi, India, participated in this study. The students were divided into five groups, each consisting of 30 students from both private and government schools. The study assessed three motor fitness components: strength (measured by the standing broad jump), speed (measured by a 50-meter sprint), and cardiovascular endurance (measured by an 800-meter run). The one-way ANOVA was used to identify significant differences among the groups, with post hoc LSD tests performed for pairwise comparisons. A significance level of p < 0.05 was applied to all analyses. Results. The analysis revealed statistically significant differences among the groups in all three motor fitness components: speed (F(4,145) = 27.07, p < 0.05), strength (F(4,145) = 16.93, p < 0.05), and cardiovascular endurance (F(4,145) = 75.46, p < 0.05). Post hoc analysis using the LSD test further indicated that students in each group differed significantly in strength, speed, and cardiovascular endurance when compared to one another. Conclusions. The study concludes that male students in grades nine and ten demonstrate significantly higher levels of strength, speed, and cardiovascular endurance compared to students in grades six, seven, and eight. Therefore, motor fitness programs targeting these components should be tailored differently for upper primary and secondary school students to address their distinct developmental needs.